Transboundary water resources in Afghanistan climate change and land-use implications - Shroder, John F. 1939-; Ahmadzai, Sher Jan (Amsterdam Elsevier, 2016)
Transboundary Water from Afghanistan: Climate Change, and Land-Use Implications brings together diverse factual material on the physical geography and political, cultural, and economic implications of Southwest Asian transboundary water resources. It is the outgrowth of long-term deep knowledge and experience gained by the authors, as well as the material developed from a series of new workshops funded by the Lounsbery Foundation and other granting agencies. Afghanistan and Pakistan have high altitude mountains providing vital water supplies that are highly contentious necessities much threatened by climate change, human land-use variation, and political manipulation, which can be managed in new ways that are in need of comprehensive discussions and negotiations between all the riparian nations of the Indus watershed (Afghanistan, China, India, and Pakistan). This book provides a description of the basic topographic configuration of the Kabul River tributary to the Indus river, together will all its tributaries that flow back and forth across the border between Afghanistan and Pakistan, and the basic elements that are involved with the hydrological cycle and its derivatives in the high mountains of the Hindu Kush and Himalaya.--Provided by publisher.
Contributors -- About the authors -- Foreword to transboundary water resources in Afghanistan -- Preface -- Introduction. 1 Introduction to physical characteristics of water : Characteristics of the regional hydrological cycle / J. Shroder -- Hydrogeography (drainage basins and rivers) of Afghanistan and neighboring countries / J. Shroder -- Ground-water geology of Afghanistan / L. Sinfield, J. Shroder -- Development of water resources in the Kabul River Basin / N. Eqrar, J. Shroder -- H₂O hazards, risks, and disasters in Afghanistan and surrounding countries / J. Shroder -- Characteristics and implications of climate change in Afghanistan and surrounding regions / J. Shroder. 2 Water-management issues in Central and South Asia : Modern water management issues in Central and Southwest Asia / J. Shroder -- Introduction to the indigenous water-management system in Afghanistan / S.J. Ahmadzai -- Dams in Afghanistan / A.K. Stewart -- Water quality matters / P. McNamara -- Issues of hydrologic data collection by remote sensing in Afghanistan and surrounding countries / J. Shroder -- Afghanistan water treaties and relevant international water law / J. Shroder -- Hydro-cognizant capacity-building in Afghanistan / J. Shroder -- Hydro-hegemony in Afghanistan and surrounding countries / J. Shroder -- Water in Islam / J. Shroder -- Water and the opium economy in Afghanistan / J. Shroder -- Hydropolitics of Afghanistan and its future / S.J. Ahmadzai -- Future of water management in Afghanistan: capacity building, risk assessment, cooperation, and good water governance / J. Shroder. 3 Distance learning in Central and South Asia : Distance learning modules for water / J. Shroder -- Concluding transboundary water activities / J. Shroder. Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Water resources development -- Afghanistan; Electronic books